1998
DOI: 10.1001/archotol.124.5.513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluticasone in Severe Polyposis

Abstract: Fluticasone and beclomethasone aqueous nasal sprays are effective in treating the symptoms of severe nasal polyps. There was some evidence that the group treated with FPANS responded more quickly to intervention and that the magnitude of the response was greater than in the group receiving beclomethasone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(114 citation statements)
references
References 14 publications
0
109
0
5
Order By: Relevance
“…Nasal peak expiratory flow is a less useful measurement and therefore not recommended over inspiratory flow (60). Potential disadvantages such as that this method measures both sides together are mentioned (61,62). One could easily measure one side by occlusion of one nostril, yet such results have not been published, validated or correlated with perceived severity.…”
Section: Objective Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal peak expiratory flow is a less useful measurement and therefore not recommended over inspiratory flow (60). Potential disadvantages such as that this method measures both sides together are mentioned (61,62). One could easily measure one side by occlusion of one nostril, yet such results have not been published, validated or correlated with perceived severity.…”
Section: Objective Methodsmentioning
confidence: 99%
“…Peak nasal inspiratory flow measurement has been used in several studies to determine nasal patency (64) with comparable sensitivity to acoustic rhinometry (65,66) and rhinomanometry (61,67,68). A strong positive correlation has been described between PNIF and the subjective sensation of nasal obstruction determined by means of questionnaires (44,69,70).…”
Section: Objective Methodsmentioning
confidence: 99%
“…The primary end point of this study was the reduction in NP score 19,20 at 8 weeks after the first dosing (1 month after the second dose). This total polyp score (TPS) is the sum of the right and left nostril scores, as evaluated by means of nasal endoscopy.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Other studies in patients with severe or bilateral polyposis found evidence of similar efficacy and tolerability of fluticasone propionate or beclomethasone dipropionate, with some evidence that fluticasone had a more rapid onset of action. [100][101][102] However, these reports lack the kinds of sizable effects that can be translated into practical application in a clinical setting. 103 The largest of these studies included fewer than 150 patients, with most enrolling fewer than 100 individuals, and the longest study was of only six months' duration.…”
Section: Acute Rhinosinusitis and Nasal Polyposis: Association With Amentioning
confidence: 99%